PENGARUH BLACK CARBON DAN SULFUR TERHADAP KOEFISIEN GRIP BAHAN BAN LUAR DENGAN BATIKAN BULAT DI LINTASAN ASPAL PADA KONDISI KERING DAN BASAH - Ariyanto, Agus, Ir. Pramuko IP, MTM. Alfatih H, ST. MT, Muh Alfatih Hendrawan,ST.,MT, Ir. Agus Hariyanto, MT (2016)
This study aims to determine the effect of black carbon and sulfur to the grip coefficient of the tire material with round grooves on both wet and dry tarmac. Tires are an important part of the vehicle, and is used to reduce ibrations caused by road surface irregularities, as well as provide stability between the vehicle and the ground to increase speed and facilitate the movement of. Tire works by utilizing surface friction force with the road surface, the friction force is referred to as grip. The materials used to make the compound is RSS natural rubber and synthetic rubber is mixed with chemicals carbon black, white oil, ZnO, strearic acid, paraffin wax, MBTS, coumarone resin and sulfur. The materials are mixed using two rolling machine mixing to form a sheet. Before the vulcanization process of compound testing rheometer to determine the maturity value. Once that is done the hardness testing using test equipment shore A hardness testing with ISO standards. Tensile test by using a rubber test equipment testing equipment with ISO standards. The coefficient of grip and wear testing using test equipment tire grip with the basic principle of the power equation. To test the grip and wear testing we add a constant load of 16.2 kg with a time of 30 minutes. From the research esults show that the coefficient of grip material testing tires with round grooves, of the four variations of the compound showed the highest coefficient of grip on compound 1 and the lowest in the compound 3. On testing the wear condition of dry and wet asphalt, compound 1 has the ighest wear values compared to other compounds.